Nomogram model of functional outcome for endovascular treatment in patients with acute basilar artery occlusion - Li, Lei; Lv, Jin; Han, Jian-jia; Gao, Yuan; Yan, Zhao-xuan; Wu, Qi; Zhang, Xiao-li; Gao, Feng (Frontiers in Neurology, 2023)
Background and purpose The efficacy and safety of endovascular treatment (EVT) in acute basilar artery occlusion (ABAO) has been confirmed by four randomized clinical trials. Nevertheless, the predictors of a 90-day favorable outcome after EVT have not been elucidated. We attempted to establish a nomogram for the prediction of a 90-day favorable outcome in ABAO patients with EVT. Methods Clinical data of ABAO patients with EVT were obtained from two nationwide clinical trial registries in China. Factors associated with a 90-day favorable outcome were screened by multivariable step-wise regression on the basis of univariable analysis. A nomogram was established to predict 90-day favorable outcome after EVT. Results The proportion of ABAO patients with a favorable outcome was 41.53% (157/378). Seven variables, including baseline National Institutes of Health Stroke Scale (NIHSS) <20 [odds ratio (OR): 8.330; P-value < 0.0001], posterior circulation Alberta Stroke Program Early CT (pc-ASPECT) score ≥7 (OR: 1.948; P-value = 0.0296), Pons-Midbrain Index (PMI) score < 2 (OR: 2.108; P-value = 0.0128), Posterior Circulation Collateral Score (PC-CS) ≥5 (OR: 3.288; P-value < 0.0001), local anesthesia (OR: 0.389; P-value = 0.0017), time from onset to recanalization (OTR) <330 min (OR: 2.594; P-value = 0.0013), and no occurrence of early neurological deterioration (END; OR: 0.039; P-value < 0.0001) were included into the nomogram, with C-index values of 0.8730 and 0.8857 in the training and the internal validation set, respectively. Conclusions The proposed nomogram provided a reliable prognostic scale, which can be employed in clinical settings for the selection and clinical management of ABAO patients. Registration https://www.clinicaltrials.gov, identifier: NCT03370939.